PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING DENGAN TEKHNIK MIND MAPPING PADA PEMBELAJARAN MATEMATIKA KELAS IX MTsN SUNGAYANG - Dinata, Desrion Surya; Desmita, Desmita; Kurnia, Lely (Jurnal Pembelajaran MIPA, 2014)
This study aims to determine the students mathematics learning outcomes with the application of quantum teaching learning model with mind mapping techniques in class IX MTsN Sungayang 2013-2014 school year. This is a quasi-experimental study, the design of randomized controlled group only design. Other research procedures can be divided into three stages: preparation, execution and completion. The research instrument used is the achievement test. The data analysis technique used is the t test. The results show the value of the research hypothesis was accepted with a P-Value of 0.05. The finding is due to the influence of the characteristics of the application of quantum teaching learning model with mind mapping techniques. The application of this model will lead to the learning atmosphere will be more fun and also enhance students understanding of mathematical concepts. Joyful learning will improve students understanding of the material. Research hypotheses that have been proposed in this study received. Therefore concluded, student learning outcomes in the experimental class (quantum teaching learning model with mind mapping technique) is better than the control class (conventional).Key words: quantum model of teaching, mind mapping, learning mathematics